Sharing local ecological knowledge as a human adaptation strategy to arid environments: Evidence from an ethnobotany survey in Morocco. (April 2016) - Blanco, Julien; Carrière, Stéphanie M.
Abstract: In order to cope with uncertainty, human populations living in drylands have developed social-risk management strategies (SRMS) and own extended ecological knowledge (LEK), which contributes to their resilience and adaptive capacity. The aim of this study was to address LEK distribution and variability and to discuss LEK adaptation to drylands. Through ethnobotanical interviews and vegetation surveys in a Saharan Moroccan village, we tested the hypothesis that LEK is shaped by plant apparency and by SRMS. Out of 164 plants, 68 were useful for 126 distinct uses. Plant cultural value obtained from free-lists was positively correlated with plant use value. Plant apparency was positively correlated with plant cultural value, which corroborated the ecological apparency hypothesis. No effect of age or gender on LEK was observed. In contrast, permanently-settled people had a lower level of knowledge than former nomads. The relative intracultural homogeneity of LEK suggests a reciprocal exchange network system strategy at the village scale, which may contribute to human adaptation and resilience to arid environments and to global changes. Nevertheless, LEK seemed interlocked with subsistence activities and with a mobile lifestyle. Conserving this lifestyle may thus be crucial for people's resilience in a context of an uncertain future. Highlights: We assessed LEK variability within a village and the influence of plant apparency. LEK varied according to plants and was positively correlated with plant apparency. Socio-economic factors, including age and gender, did not explain LEK variability. LEK was lower for permanently-settled people, thus linked to traditional lifestyle. LEK homogeneity between age and gender may enhance people resilience to risk.